The numerical solution of fifth-order boundary value problems with sixth-degree B-spline functions - Çaglar, HN; Çaglar, SH; Twizell, EH (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
The numerical solution of fifth-order, nonlinear boundary-value problems with two-point boundary conditions is considered. A sixth-degree B-spline approximation is used to construct the numerical method, the coefficients of which are detailed in a table. The method is tested on two problems, one linear and one nonlinear. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: fifth-order boundary-value problems; B-splines; numerical methods; MODELING VISCOELASTIC FLOWS; Mathematics